A Legal Analysis of the United States' Unilateral Import Tariff Policy on Indonesia's Trade Relations from the Perspective of International Trade Law - Fani Zahara Suwarno Putri; Ratu Mawar Kartina (Asian Journal of Social and Humanities, 2026)
The global trading system has increasingly faced challenges arising from unilateral tariff measures adopted by major economies, creating tensions between national trade interests and obligations under international trade law. The United States' reciprocal import tariff policy, which initially imposed a 32% tariff on Indonesian products, raised legal concerns regarding its consistency with the principles of non-discrimination, Most-Favored-Nation (MFN) treatment, and tariff-binding commitments under the World Trade Organization (WTO) framework and the General Agreement on Tariffs and Trade (GATT) 1994. This study aimed to analyze the legal implications of the United States' unilateral import tariff policy toward Indonesia and to examine Indonesia's legal and strategic responses to protecting its export interests. This research employed a normative legal research method using statutory, conceptual, and comparative approaches. The analysis was based on primary legal materials, including the General Agreement on Tariffs and Trade (GATT) 1994, WTO agreements, the Vienna Convention on the Law of Treaties, official government documents, and relevant legal decisions, supported by secondary literature and illustrative data from export-sector stakeholders. The findings indicated that the unilateral tariff policy could conflict with Articles I and II of the GATT 1994 if the differential treatment and additional tariffs were not justified under applicable WTO exceptions. The study also found that Indonesia's diplomatic response through the Agreement on Reciprocal Trade reduced tariff pressures but required careful evaluation regarding its regulatory commitments and implications for national policy interests. This research concluded that Indonesia needed a comprehensive strategy combining WTO dispute settlement mechanisms, bilateral diplomacy, export diversification, and strengthened domestic competitiveness to safeguard its national trade interests within the rules-based international trading system.